Implementasi Kegiatan Ngaji Dalam Meningkatkan Literasi Al-Qur’an Anak Di TPA At-Taqwa Desa Gung Pinto - Asma, Nurul; Nasution, Mawaddah (Journal of Community Sustainability, 2025)
This Independent Real Work Lecture (KKN) activity aims to improve children's Qur'an literacy at the At-Taqwa TPA, Gung Pinto Village through the implementation of structured and educational activities. The activity was carried out on September 1-17, 2025 involving around 30-40 children aged 6-12 years. The approach used is qualitative descriptive with a participatory method, where KKN students play the role of facilitators and companions of TPA teachers in the implementation of daily prayer activities. The learning process includes the initial observation stage, the implementation of ngaji using talaqqi, tahsin, and murojaah methods, and evaluation of children's learning outcomes. The results of the activity showed that there was an increase in children's ability to recognize hijaiyyah letters, improve the makhraj of letters, and read the Qur'an more tartilly. In addition, children's motivation and participation also increase along with a fun and interactive approach. This activity makes an important contribution in building synergy between students, TPA teachers, and the community as a form of strengthening community-based Islamic education and developing a culture of Qur'an literacy at the local level.